Upconversion carbon quantum dots as visible light responsive component for efficient enhancement of photocatalytic performance - Ke, J.; Li, X.; Zhao, Q.; Liu, B.; Liu, Shaomin; Wang, Shaobin (Academic Press, 2017)
It finds that CQDs synthesized by hydrothermal method possess obvious upconversion properties that could transfer low energy photons to high energy photons, resulting in enhanced visible light response and utilization. Herein, carbon quantum dots (CQDs) modified TiO2 photocatylysts were successfully prepared by a facile sol-gel method. Photophysical and surficial properties of the as-prepared composite photocatalyst were investigated in details. Furthermore, photocatalytic performance was tested by degrading methylene blue (MB) under visible light irradiation. The degradation efficiency of methylene blue (MB) is as high as 90% within 120 min, which is 3.6 times higher than that of pure TiO2.